2016
DOI: 10.1242/dev.131466
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Smad2 but not Smad3 is required to mediate TGF-β signaling during axolotl limb regeneration

Abstract: Axolotls are unique among vertebrates in their ability to regenerate tissues, such as limbs, tail and skin. The axolotl limb is the most studied regenerating structure. The process is well characterized morphologically; however, it is not well understood at the molecular level. We demonstrate that TGF-β1 is highly upregulated during regeneration and that TGF-β signaling is necessary for the regenerative process. We show that the basement membrane is not prematurely formed in animals treated with the TGF-β anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 82 publications
(100 reference statements)
1
51
0
1
Order By: Relevance
“…To further investigate the role of SMADs in TGF‐β1 induced migration and MMP‐2/‐9 induction, we performed knockdown experiments in Schwann cells. We found that TGF‐β1‐induced MMP‐2 secretion was SMAD2‐dependent, in agreement with other studies (Piek et al, ; Meng et al, ; Denis et al, ). These results suggest that inhibition of the canonical TGF‐β1 pathway blocks cell migration and invasion by preventing the activation of SMAD2.…”
Section: Discussionsupporting
confidence: 93%
“…To further investigate the role of SMADs in TGF‐β1 induced migration and MMP‐2/‐9 induction, we performed knockdown experiments in Schwann cells. We found that TGF‐β1‐induced MMP‐2 secretion was SMAD2‐dependent, in agreement with other studies (Piek et al, ; Meng et al, ; Denis et al, ). These results suggest that inhibition of the canonical TGF‐β1 pathway blocks cell migration and invasion by preventing the activation of SMAD2.…”
Section: Discussionsupporting
confidence: 93%
“…As downstream effectors of all three pathways interact in development and tumorigenesis (McNeill and Woodgett, 2010; Attisano and Wrana, 2013), it is likely that synergy between these pathways is essential for early blastemal cell establishment and maintenance. Interestingly, TGF-β signaling, which is necessary for axolotl limb regeneration (Levesque et al, 2007;Denis et al, 2016), was specifically active in dividing cells. Our data further suggest that TGF-β signaling is sustained through autocrine feedback in early dividing cells, which exhibit exclusive upregulation of tgf-β1, tgf-β1r and smad-2, as well as regulators and direct targets, including ltbp1, twist1 and snail-1.…”
Section: Discussionmentioning
confidence: 99%
“…Smad2 is activated when mesenchymal cells are migrating and proliferating to give rise to the regenerative structure known as “blastema”. We also demonstrated that the activity of Smad3 is not essential for the regeneration process to occur and we showed that overexpression of the protein leads to apoptosis (Denis et al., ). In addition, the immune response is weak following amputation which is reminiscent of what is observed in the Smad3 KO mouse (Mescher & Neff, ).…”
Section: Tgf‐β Target In Ecmmentioning
confidence: 81%
“…In the Axolotl regeneration process and skin wound healing MMPs are also observed (Ashcroft et al., ; Denis et al., ; Seifert et al., ; Yang & Bryant, ; Yang, Gardiner, Carlson, Nugas, & Bryant, ). Some of these enzyme are regulated by tgf‐ β (namely MMP2 and MMP9) (Denis et al., ), and they are essential for this process because inhibition of MMP activity leads to a loss of regenerative capacity (Vinarsky, Atkinson, Stevenson, Keating, & Odelberg, ). These observations point out that regulation of collagens and enzymes responsible for their remodeling is coregulated.…”
Section: Tgf‐β Target In Ecmmentioning
confidence: 99%